Are leaders defined by followers? Role of follower's ILT and the mediating influence of LMX on follower outcomes. Issue 1 (14th March 2016) - Rahn, Doug L; Jawahar, I.M.; Scrimpshire, Alex J.; Stone, Thomas
Abstract : Purpose: – The purpose of this paper is to cast followers in an active role, and proposes a research model in which follower's implicit leadership theory (ILT) congruence (ILT congruence) influences perceptions of transformational leadership (TL) and the quality of leader-member exchange (LMX) relationship. In addition, the authors expect LMX to mediate the influence of ILT congruence and TL on outcomes. Design/methodology/approach: – The research model was tested with data collected at three different points in time from 210 newly hired employees. Results of structural equation modeling provided strong support for the overall model. Findings: – This study focussed on extending the understanding of leader-follower relationships. First, ILTs measured on the first day of employment shaped new entrants' perceptions of TL measured 30 days after date of hire. Second, both ILT congruence and TL influenced the quality of LMX measured approximately 90 days from followers' date of hire. As expected, LMX fully mediated the influence of ILT congruence and perceptions of TL on the dependent variables of turnover intentions, organizational identification and perceived organizational support (POS). Practical implications: – Organizations should focus on measuring and developing LMX quality during the early phases of a follower's socialization into the organization. Consistent with other research (Erdogan and Liden, 2002), LMX was a significant predictor of turnover intentions, organizational identification, and POS. Given the cost of turnover, organizations focussed on developing high quality LMX relationships could realize dramatic results. Originality/value: – This study extends prior research by showing LMX fully mediates the influence of followers' ILTs and transformational leader behaviors on POS, organizational identification and turnover intentions. By using data collected at three points in time from new employees, the authors demonstrated the effect of ILT congruence on the early development of LMX. Additionally, the results showed high ILT congruence leads followers to perceive their leaders as more transformational. Finally, data show the effects of ILT congruence and TL perceptions on turnover intentions, POS and organizational identification were fully mediated by LMX.